Ciências no Ensino Fundamental: concepções de professores - limites e possibilidades - Duarte, Marcelo da Silva Alcantara (2017)
The present work aims to investigate how science education reaches the student seeking to understand the trajectory of scientific concepts and to draw a profile of the conception of science that the elementary school teacher has. As a theoretical support we used the readings of several authors such as John Dewey, Antonio Cachapuz, Gil Perez, Ana Maria Pessoa de Carvalho, Myriam krasilchik among others who gave body and meaning to this research. It was essential to listen to the teachers through interviews, as well as the observations of science classes, identifying the teacher's conceptions about science. This allowed to recognize some distorted visions of science and other factors that are possible obstacles like; Teacher training, physical space of the school for practical classes, among others. In this sense, this research is of great relevance in order to seek to understand the trajectory of scientific concepts and to draw a profile of the conception of Sciences that the elementary school teacher possesses, in order to seek to know how science teaching takes place, as Science is Presented to the student. Thus, the research aims to contribute to the student reaching the High School with a conception of science suitable for their continuity of study, ie to understand the more complex concepts, coming from the disciplines of Biology, Chemistry and Physics, aiming for an improvement of quality Of primary and secondary education